A 28-year single institution experience with primary skin malignancies in the pediatric population. Issue 1 (1st February 2022) - Kuruoglu, Doga; Weissler, Jason M.; Bustos, Samyd S.; Moran, Steven L.; Davis, Dawn M. R.; Bite, Uldis; Mardini, Samir; Baum, Christian L.; Otley, Clark C.; Brewer, Jerry D.; Lehman, Julia S.; Sharaf, Basel
Abstract: The aim of this study is to report our institution's experience with pediatric skin malignancies. A single institution retrospective review of pediatric patients with a primary skin malignancy from 1992 to 2020 was performed. Demographics, tumor characteristics and treatment outcomes were reviewed. Ninety-nine patients with 109 primary malignant skin lesions were reviewed. The most common lesion was malignant melanoma [MM] ( n  = 50, 45.9%). Compared to non-melanoma skin cancer (NMSC), MM were more likely to present on trunk or extremities ( p =.01, OR = 3.2), and be misdiagnosed ( p =.03, OR = 2.7). NMSC were more common in the head and neck region ( p =.01, OR = 3.2), and were associated with a personal history of skin cancer ( p =.0005, OR = 17.1) or a known risk factor ( p =.04, OR = 2.5). Patients with MM were 12.4-times more likely to develop metastatic disease compared to NMSC ( p <.0001). Increased Breslow's thickness also increased the odds of developing metastatic disease ( p =.03, OR = 1.6 per 1-mm increase). Interval time between lesion recognition and diagnostic biopsy or surgical treatment did not impact overall survival. Malignant melanoma was the most common malignancy in our cohort, followed by basal cell carcinoma. Malignant melanoma was the most likely tumor to be misdiagnosed and/or metastasize. Treatment delays did not impact risk of metastasis, recurrence or survival rate, though some patients succumbed to disease. These results may be attributed to small sample size or the biology of melanoma in pediatric patients. Awareness of skin malignancies in the pediatric population is imperative to providers and the public, with low threshold for specialty consultation and excision when warranted.